Implementation considerations when expanding health worker roles to include safe abortion care: a five-country case study synthesis - Claire Glenton; Annik M. Sorhaindo; Bela Ganatra; Simon Lewin (BMC, 2017)
Abstract Background Allowing a broader range of trained health workers to deliver services can be an important way of improving access to safe abortion care. However, the expansion of health worker roles may be challenging to implement. This study aimed to explore factors influencing the implementation of role expansion strategies for non-physician providers to include the delivery of abortion care. Methods We conducted a multi-country case study synthesis in Bangladesh, Ethiopia, Nepal, South Africa and Uruguay, where the roles of non-physician providers have been formally expanded to include the provision of abortion care. We searched for documentation from each country related to non-physician providers, abortion care services and role expansion through general internet searches, Google Scholar and PubMed, and gathered feedback from 12 key informants. We carried out a thematic analysis of the data, drawing on categories from the SURE Framework of factors affecting the implementation of policy options. Results Several factors appeared to affect the successful implementation of including non-physician providers to provide abortion care services. These included health workers' knowledge about abortion legislation and services; and health workers' willingness to provide abortion care. Health workers' willingness appeared to be influenced by their personal views about abortion, the method of abortion and stage of pregnancy and their perceptions of their professional roles. While managers' and co-workers' attitudes towards the use of non-physician providers varied, the synthesis suggests that female clients focused less on the type of health worker and more on factors such as trust, privacy, cost, and closeness to home. Health systems factors also played a role, including workloads and incentives, training, supervision and support, supplies, referral systems, and monitoring and evaluation. Strategies used, with varying success, to address some of these issues in the study countries included values clarification workshops, health worker rotation, access to emotional support for health workers, the incorporation of abortion care services into pre-service curricula, and in-service training strategies. Conclusions To increase the likelihood of success for role expansion strategies in the area of safe abortion, programme planners must consider how to ensure motivation, support and reasonable working conditions for affected health workers.